2019
DOI: 10.15835/buasvmcn-vm:2019.0019
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Parasites of Free-Range Chickens – A Worldwide Issue

Abstract: Gastrointestinal parasites with direct and/or indirect life cycles, namely Eimeria spp., Ascaridia galli, Heterakis gallinarum and Capillaria spp., are responsible for the most frequent and heavy economic losses in aviculture. The current review aimed to collect information about gastrointestinal parasites affecting poultry, as well as, research studies regarding parasitic diseases in free-range chicken production. From the references used in this review, 20% highlight research studies correlating prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 10 publications
1
12
0
8
Order By: Relevance
“…Free-range poultry and captive wild birds are commonly housed in limited areas with high animal stocking and access to the environment and co-habit with other bird species and wild avifauna, consequently being exposed to a wide variety of generalist or host-specific gastrointestinal (GI) parasites, namely coccidia and helminths, which are still responsible for severe health and economic concerns in poultry farms and zoological collections worldwide [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Free-range poultry and captive wild birds are commonly housed in limited areas with high animal stocking and access to the environment and co-habit with other bird species and wild avifauna, consequently being exposed to a wide variety of generalist or host-specific gastrointestinal (GI) parasites, namely coccidia and helminths, which are still responsible for severe health and economic concerns in poultry farms and zoological collections worldwide [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In these mixed infections, it was more frequently observed that more than 90% of them had nematode and cestode species together. Several authors still seek to establish a correlation between the prevalence of helminths and some climatic variables, such as temperature, humidity and precipitation (Lozano et al, 2019). The climatic conditions of the city of Viçosa (average temperature 20.6 °C and 1229mm average annual rainfall) associated with the extensive breeding system, favorably influence the maintenance of direct biological cycle parasites, as well as the ubiquitous distribution of intermediate hosts of cestodes and trematodes (Permin et al, 1999;Ruff, 1999;Silva et al, 2018;Thapa et al, 2015;Vieira et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive poultry production systems are intended to promote the natural behavior of animals, and consumers play a considerable role in their recent preference for healthier and more natural food sources (Lozano et al, 2019). However, these systems are characterized by high levels of helminth infections, usually accompanied by reduced production performance and behavioral changes which could indicate reduced animal welfare in chickens (Tamara et al, 2019;Thapa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations